2008
DOI: 10.17221/350-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lycopene supplementation on lipid profile and meat quality of broiler chickens

Abstract: Lycopene is a carotenoid that is mostly present in vegetables and in some fruit species as a red pigment (pineapple, orange, grapefruit, tomato, sweet pepper, strawberry). Tomatoes and products from tomatoes are the main source of lycopene while the tomato skin is a rich source of lycopene. Lycopene is extraordinarily efficient in the control of degenerative diseases, it is a preventive against cardiovascular diseases and cancer of prostate gland, digestive tract, skin, it decreases a risk of the cancer of pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 34 publications
3
10
0
2
Order By: Relevance
“…However, it is to note that our preliminary experiments aimed at the investigation of nutrient and energy utilization in pigs (Nitrayová et al, 2009) and at demonstration of the influence of physiologically active substances in broiler chickens Ševčíková et al, 2008) were not successful.…”
Section: And Discussionmentioning
confidence: 89%
“…However, it is to note that our preliminary experiments aimed at the investigation of nutrient and energy utilization in pigs (Nitrayová et al, 2009) and at demonstration of the influence of physiologically active substances in broiler chickens Ševčíková et al, 2008) were not successful.…”
Section: And Discussionmentioning
confidence: 89%
“…and cardiovascular disease by regulating lipid metabolism [8][9][10]. Lycopene or lycopene-enriched plant materials in poultry diet also showed positive regulation effect on serum lipids levels [11][12][13][14].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Lycopene is a carotenoid present in vegetables and ripe fruit and has been proved to be the most potent antioxidant among various common carotenoids (Di Mascio et al., ). Several dietary studies have shown that diets rich in lycopene were significantly correlated with antioxidants plasma level and associated with decreasing risk of diseases (Ševčíková et al., ; Mangiagalli et al., ).…”
Section: Introductionmentioning
confidence: 99%